An amicyanin C-terminal loop mutant where the active-site histidine donor cannot be protonated - Remenyi, Rainer; Comba, Peter (Journal of biological inorganic chemistry, 2001)
A novel blue copper protein was constructed by replacing the C-terminal loop of amicyanin (Paracoccus versutus) by the homologous loop of rusticyanin. The C-terminal loop of both amicyanin and rusticyanin contains three (His, Cys, Met) of the four copper ligands. The amicyanin mutant exhibits all spectroscopic properties normally encountered for blue copper sites. The midpoint potential (369 mV) is the highest reported value for an amicyanin mutant. Cyclic voltammetry and NMR studies of the reduced form indicate that, in contrast to wild-type amicyanin and all amicyanin mutants described so far, the C-terminal histidine ligand does not protonate in the accessible pH range (pK a<4.5).